2020
DOI: 10.1002/wer.1406
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater treatment, reuse, and disposal‐associated effects on environment and health

Abstract: This paper presents the review of the literature published in the year 2019 related to treatment and reuse of wastewater and effects on the environment and human health. The scientific review on the treatment and reuse of wastewaters is divided into various sections in the paper. The review sections cover wastewater management, reuse, removal of microorganisms, and chemical constituents. Besides, the review also covers research focused on wastewater treatment plants, disposal, and the management of wastewater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…FSM is considered an insignificant aspect of environmental sanitation, and discharging FS in water bodies, lagoons, and the environment is regularly considered the normal and proper way of dealing with FS. At the same time, through the utilization of sludge in the reclamation of agricultural land or fertilizer contaminants, their metabolites and transformation products [ 98 ] are circulating in the environment [ 73 , 99 102 ]. These substances are toxic; hence, the possibility of causing harm to humans or the environment is rising.…”
Section: Challenges Of Sewerage Systems In Sub-saharan Africamentioning
confidence: 99%
“…FSM is considered an insignificant aspect of environmental sanitation, and discharging FS in water bodies, lagoons, and the environment is regularly considered the normal and proper way of dealing with FS. At the same time, through the utilization of sludge in the reclamation of agricultural land or fertilizer contaminants, their metabolites and transformation products [ 98 ] are circulating in the environment [ 73 , 99 102 ]. These substances are toxic; hence, the possibility of causing harm to humans or the environment is rising.…”
Section: Challenges Of Sewerage Systems In Sub-saharan Africamentioning
confidence: 99%
“…In 1992, Kim and Gee published a work in "Water Environmental Research" prospecting the relevant rule of biotechnology for the treatment of hazardous wastes (Kim & Gee, 1992). Approximately 30 years later, we know that bacteria can support the sustainable implementation of a circular economy by increasing the performances of wastewater treatments for water reuse (Choudri, Al-Awadhi, Charabi, & Al-Nasiri, 2020); controlling GHG emissions by the capture and/or sequestration of CO 2 or reducing its global pressures in the atmosphere (Koh & Shaw, 2018); producing hydrogen, biomethane and different forms of bioenergy (Sheehan et al, 2018); and introducing other amazing solutions with promising applications for global sustainability (Chang, DiGiovanni, & Mei, 2019).…”
Section: Vincenzo Naddeomentioning
confidence: 99%
“…However, majority of parts of the world are facing worst water shortage, and it has been reported that one in every five persons has no access to safe drinking water (WHO, 2015). According to previous reports, fresh water reservoirs will lose completely in near future due to rapid increase in population, urbanization and industrialization, climate change, water pollution, global warming, and loss of renewable water reservoirs (Choudri et al, 2020;Kumar & Chopra, 2018;Li et al, 2014;Naz et al, 2016;Rehman et al, 2021). Moreover, industrial consumption of fresh water for various processing steps releases huge amount of untreated wastewater into aquatic bodies affecting both flora and fauna as well as diminishing clean water reservoirs which is an alarming situation (Ali et al, 2021;Al-Najar et al, 2022;Cabral-Pinto et al, 2020;Kurwadkar et al, 2020;Rehman et al, 2012;Sehar et al, 2020Sehar et al, , 2021Zhu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%